2022
DOI: 10.1017/wet.2022.61
|View full text |Cite
|
Sign up to set email alerts
|

Control of glyphosate-resistant horseweed with Group 4 herbicides in soybean

Abstract: Little information is available on the efficacy of Group 4 herbicides for glyphosate-resistant (GR) horseweed management in soybean. Five field research trials were established in growers’ fields from 2020 to 2021 to determine GR horseweed control with Group 4 herbicides applied pre-plant (PP) alone and in a mixture. There was minimal soybean injury (≤4%) with herbicides evaluated. Dicamba, 2,4-D, or halauxifen-methyl applied PP, controlled GR horseweed 92-96, 73-76, and 85-89%, respectively. The mixtures of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
0
0
Order By: Relevance
“…Economic analysis revealed that the combined herbicide treatment resulted in the highest economic returns compared to individual herbicide applications and the control. Despite the slightly higher initial investment associated with the combined herbicide treatment, the increased wheat yield and quality outweighed the additional costs, resulting in greater net profits for farmers [17][18][19].…”
Section: Resultsmentioning
confidence: 99%
“…Economic analysis revealed that the combined herbicide treatment resulted in the highest economic returns compared to individual herbicide applications and the control. Despite the slightly higher initial investment associated with the combined herbicide treatment, the increased wheat yield and quality outweighed the additional costs, resulting in greater net profits for farmers [17][18][19].…”
Section: Resultsmentioning
confidence: 99%